NUMERICAL MODELLING OF CURRENT ON WAVE DRIFT LOAD OF A SHIP SHAPED OFFSHORE STRUCTURES (CASE STUDY – EXCRAVOS IN WEST AFRICAN OFFSHORE) - Joshua, Abam, Tamunopekere; Ahamefula, Agbakwuru, Jasper; Olabisi, Adeyemi, I. (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
On account of the piecemeal reduction of oil and gas resources onshore and shallow waters,oil exploration is gradually moving into deeper waters. One of the major means of exploration of theseresources is by ship-shaped offshore structures. Owing to marginal field and the increment of depths ofexploration, there comes the need for the reusable, re-locatable and field-independent ship-shapedoffshore structures. They include FPSO, FLNG, FSO, drill ships etc. A usual phenomenon thesestructures face at their location is drifting i.e. losing its course. The research presents the numericalanalysis of sea loads on these structures. It focuses more on waves and current effects. This work uses atheory developed by Faltenses 1990 and modified by Said in 2010 and extended the theory to verify theeffects of current on second-order wave force on an operational FSO LPG ESCRAVOS in West Africa,Nigeria. This FSO is co-owned by the Nigerian government and Chevron Nigeria limited. Data used forcomputation of the current forces were obtained from the Oil Companies International Marine Forum of2014. Computations were carried out in irregular wave’s conditions data prevalent in Escravos, OffshoreNigeria. Based on it, steady drift motion responses and effect of the current forces are examined.Environmental conditions, such as effect of current velocity, current forces and current angle of attackon wave drift load are analyses, which significantly affected the FSO motion in surge, sway and yawmoments. It is found that the effect of current forces is quite significant when the current velocity isincreased. In this numerical analysis, while the current velocity is increased to 2.0 meter/seconds (3.90knots), the impact on FSO motion is quite significant, which should be taken into consideration from thepoint of view of design, safety, failure of mooring systems, operating responses, production shut downand the positioning of the FPSO. The results of the discussion conform to facts about sea loads and itseffects.